Educational Leadership in Building Student Character and Dicipline - Fenita Sari Purba (PT ARFA DIGITAL TECHNOLOGY, 2025)
Education plays an essential role in shaping human character and competence. In the digital era, teachers encounter new challenges that require the ability to adapt to technology and innovate in learning. Teacher professionalism is no longer measured solely by teaching skills but also by digital competence, creativity, and commitment to educational ethics and values. This study examines the various challenges and strategies teachers employ to face the digital era, highlighting the importance of competency development, continuous training, and technology integration in the teaching and learning process. The findings indicate that teachers must become lifelong learners. Through continuous learning, teachers function as facilitators, innovators, and moral role models in modern education.